Peri-implant diseases triggered by oral microdysbiosis: pathogenesis and precision intervention strategies - Chen, Gang; Zhao, Xin; Yang, Bin; Gu, Hongzheng (Frontiers in Microbiology, 2025)
Peri-implant disease is a chronic infection-induced inflammation condition affecting tissues around dental implants, categorized into peri-implant mucositis and peri-implantitis. Oral microbial dysbiosis plays an important role in this disease. Currently, researchers face three challenges in establishing the pathogenic link between peri-implant disease and microdysbiosis: (1) elucidating the underlying molecular mechanisms; (2) Clarifying causal links between host and microbiome; and (3) Identifying secondary microbial changes during disease progression. In this review, we systematically classify dysbiosis from a conceptual perspective and outline the immunological associations within each category. We further elaborate on the causes of bacterial dysbiosis and analyze its potential implications for clinical treatment strategies. At the molecular level, understanding the origins, intrinsic and environmental regulatory mechanisms, and downstream effects may be conducive to develop microbiome targeted therapies. This research direction is of great significance for promoting precision medicine in peri-implant disease.